2018
DOI: 10.1111/wrr.12682
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction aggravated impaired cutaneous wound healing in diabetic mice

Abstract: Renal dysfunction has been associated with poor outcomes of wound healing in the diabetic population. The purpose of this study was to create an excisional wound healing model in diabetic mice with renal dysfunction to investigate the combined effects of diabetes and nephropathy on cutaneous ulcers. Renal impairment was introduced in diabetic db/db mice through unilateral nephrectomy and electrocoagulation of the contralateral kidney. Renal function was subsequently monitored with assays of blood urea nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Several inflammatory parameters are elevated in diabetic patients and constitute strong predictors of the development of this disease. The increase in inflammatory cytokine levels in the diabetic patient leads to microvascular complications, such as the development of nephropathy [9] [10]. Activated immune cells migrate and infiltrate kidney tissue locally, producing more inflammatory mediators and chemokines that recruit more immune cells to the kidney.…”
Section: Diabetic Kidney Disease (Dkd) Ou Diabetic Nephropathy (Dn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several inflammatory parameters are elevated in diabetic patients and constitute strong predictors of the development of this disease. The increase in inflammatory cytokine levels in the diabetic patient leads to microvascular complications, such as the development of nephropathy [9] [10]. Activated immune cells migrate and infiltrate kidney tissue locally, producing more inflammatory mediators and chemokines that recruit more immune cells to the kidney.…”
Section: Diabetic Kidney Disease (Dkd) Ou Diabetic Nephropathy (Dn)mentioning
confidence: 99%
“…Furthermore, quantitative polymerase chain reaction (qPCR) results showed corresponding alterations of related genes (TNF-α, IL-1β, SOD2) in wounds from db/db mice with kidney injury. Renal manipulation in this study accelerated the progress of renal impairment, which has been shown to worsen impaired skin wound healing in diabetic mice leading to a significant increase in urinary protein excretion [10] [12].…”
Section: Diabetic Kidney Disease and Wound Healingmentioning
confidence: 99%
“…The splinted full thickness model enables direct application of topical agents on the wound bed or assessment of wound healing upon systemically pharmacological treatment. In parallel to other murine wound healing models, it also allows the study of wound healing in different pathological conditions, e.g., renal dysfunction [44], using respective transgenic or knockout mice. The splinted wound model was recently applied in rats to study hypertrophic scarring [45] and to study new splint constructions [46].…”
Section: The Splinted Full Thickness Modelmentioning
confidence: 99%
“…The splinted full thickness model was used study the effects of recombinant myxoma virus-derived immune modulator M-T7 [49], of Babassu oil [50], of three-dimensional printed scaffolds and electrospun mats [51], of adult gingival multipotent mensenchymal stem cells [52], of induced pluripotent stem cells clay [53], of poly(lactic-co-glycolic acid) and vascular endothelial growth factor [54], and of renal dysfunction [44] on cutaneous wound healing.…”
Section: The Splinted Full Thickness Modelmentioning
confidence: 99%